2010
DOI: 10.1111/j.1365-2982.2009.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of serotonin 5-HT2Breceptor alters proliferation and network volume of interstitial cells of Cajalin vivo

Abstract: Background-Normal gastrointestinal motility requires intact networks of interstitial cells of Cajal (ICC). ICC numbers are maintained by a balance between cell loss factors and survival/ trophic/growth factors. Activation of 5-HT 2B receptors expressed on ICC increases ICC proliferation in vitro. It is not known whether 5-HT 2B receptors on ICC are activated in vivo. The aims of this study were to investigate if adult ICC proliferate, whether the proliferation of ICC in vivo is affected by knocking out the 5-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 45 publications
(102 reference statements)
2
63
0
Order By: Relevance
“…We know also, playing similar role, other signal paths with neuronal originated nitric oxide [5], serotonin acting through 5-HT 2B receptor [68], interleukine-9 [70], insulin and insulin-like growth factor (IGF-1) [21], heme oxygenase (HO-1) [4]. 5-HT 2B receptor is responsible for maintenance of network of ICC [59]. Its activation begins proliferation of ICC.…”
Section: Role Of Iccmentioning
confidence: 99%
“…We know also, playing similar role, other signal paths with neuronal originated nitric oxide [5], serotonin acting through 5-HT 2B receptor [68], interleukine-9 [70], insulin and insulin-like growth factor (IGF-1) [21], heme oxygenase (HO-1) [4]. 5-HT 2B receptor is responsible for maintenance of network of ICC [59]. Its activation begins proliferation of ICC.…”
Section: Role Of Iccmentioning
confidence: 99%
“…ICC express 5-HT 2B receptors, and stimulation with 5-HT (serotonin) increases ICC proliferation and numbers [27]. It has also been demonstrated that a lack of 5-HT 2B receptors decrease ICC proliferation, numbers and network volume [19]. These images were 512 Â 512 pixels, and represented physical dimensions ranging from 0.225 Â 0.225 mm to 0.318 Â 0.318 mm.…”
Section: Interstitial Cell Of Cajal Network Imaging Data 221 Imagimentioning
confidence: 99%
“…An ICC network image from a 5-HT 2B receptor KO jejunal ICC-MP dataset [19] was used as an example network to illustrate the developed metrics (figures 1a and 2b). See §2.2.1 for the detailed description of the example network image.…”
Section: Formulation Of Numerical Metricsmentioning
confidence: 99%
See 2 more Smart Citations